2021
DOI: 10.3847/psj/abfdba
|View full text |Cite
|
Sign up to set email alerts
|

Asteroid 16 Psyche: Shape, Features, and Global Map

Abstract: We develop a shape model of asteroid 16 Psyche using observations acquired in a wide range of wavelengths: Arecibo S-band delay-Doppler imaging, Atacama Large Millimeter Array (ALMA) plane-of-sky imaging, adaptive optics (AO) images from Keck and the Very Large Telescope (VLT), and a recent stellar occultation. Our shape model has dimensions 278 (−4/+8 km) × 238(−4/+6 km) × 171 km (−1/+5 km), an effective spherical diameter D eff = 222-1/+4 km, and a spin axis (ecliptic lon, lat) of (36°, −8°… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
95
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(115 citation statements)
references
References 37 publications
7
95
0
Order By: Relevance
“…This variation indicates that Psyche does not have a constant composition across the surface. The recent works (e.g., Shepard et al (2021) and Ferrais et al (2020)) also support this conclusion. In addition, Sanchez et al (2016) and Takir et al (2016) showed the presence of orthopyroxene and hydrated silicates on the surface although they do not provide strong constraints on abundances of silicates.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…This variation indicates that Psyche does not have a constant composition across the surface. The recent works (e.g., Shepard et al (2021) and Ferrais et al (2020)) also support this conclusion. In addition, Sanchez et al (2016) and Takir et al (2016) showed the presence of orthopyroxene and hydrated silicates on the surface although they do not provide strong constraints on abundances of silicates.…”
supporting
confidence: 52%
“…However,if the asteroid is a pure metal or dominantly metal-rich object, the most puzzling physical parameter is its bulk density. While the density of iron meteorites is ∼7.5 g cm −3 (Smyth & Mccormick 1995), the recent estimates of the Psyche's bulk density are all close to ∼4.0 g cm −3 (Carry 2012;Hanuš et al 2017;Drummond et al 2018;Viikinkoski et al 2018;Shepard et al 2021;Siltala & Granvik 2021;Elkins-Tanton et al 2020), which is remarkably lower than the expected value. This inconsistency may be understandable if Psyche is a rubble-pile asteroid having a very high porosity (> ∼50%).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Lutetia also has lower radar albedo than Psyche has (Shepard et al. 2015 , 2021 ). In contrast to the limited data available from the Lutetia flyby, the Psyche mission instrument package will provide much greater detail needed to identify meteorite analogs.…”
Section: Alternative Origin Scenariosmentioning
confidence: 99%
“… 2016 ) and large-scale radar albedo (Shepard et al. 2021 ) that would be spatially resolvable by GRNS if they correspond to chemical differences.…”
Section: How We Will Use Our Data To Determine Psyche’s Originmentioning
confidence: 99%